2012
DOI: 10.1088/0957-0233/23/11/115001
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale noise tuning stochastic resonance enhances weak signal detection in a circuitry system

Abstract: Stochastic resonance (SR) has been proved to be an effective way to detect a weak signal submerged in heavy background noise. This paper addresses the improvement of the SR approach to enhance the effectiveness of weak signal detection through a circuitry system. There are mainly two contributions in this study. First, the multiscale noise tuning through a filter array is designed based on the property of 1/ f process to enhance the performance of a classical SR circuitry system. Second, a practical weak signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…When the MSTSR and the SMSTSR methods are conducted to deal with the same offline signals, it can be found that both of the two methods outperform the EMD-based and the LPSR-based spectral analysis methods in processing three kinds of defective signals. The obtained experimental results show that the weak periodic signals have been enhanced successfully by the 1/ f -type noise [17]- [19]. From the running duration aspect, it can be found that the EMD method spends a large computation time but has poorer efficiency.…”
Section: B Effectiveness Of the Proposed Algorithmmentioning
confidence: 87%
See 2 more Smart Citations
“…When the MSTSR and the SMSTSR methods are conducted to deal with the same offline signals, it can be found that both of the two methods outperform the EMD-based and the LPSR-based spectral analysis methods in processing three kinds of defective signals. The obtained experimental results show that the weak periodic signals have been enhanced successfully by the 1/ f -type noise [17]- [19]. From the running duration aspect, it can be found that the EMD method spends a large computation time but has poorer efficiency.…”
Section: B Effectiveness Of the Proposed Algorithmmentioning
confidence: 87%
“…The bandwidth w j of each Filter j corresponds to the multiscale property of orthonormal WT [17]. That is as follows:…”
Section: B Filter Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the concept of SR was first put forward by Benzi et al in 1981 [1], the positive effect of SR has been widely investigated and applied in various research fields, such as physics, chemical, biological and electronic, etc. [2][3][4][5][6][7][8][9][10]. In signal detection theory, it is also called noise enhanced detection [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this phenomenon has attracted considerable attention for information transmission and detection [12,13,14,15], biological neuro analysis [16,17,18,19], and image processing [20,21,22,23]. In the mechanical engineering field, it has been theoretically investigated whether stochastic resonance can be applied to improve the efficiency of energy harvesting [24].…”
Section: Introductionmentioning
confidence: 99%